Resurfacing of the Knee Joint after Release of Contracture - Ila Saha; S. Chatterji; A. Roy (Indian Journal of Plastic Surgery)
Fifteen cases of post burn contracture of the knee were resurfaced after release of contracture by the medial head of gastrocnemius muscle and free skin graft, during the last 5 years period. It was found to be a much superior and useful method as compared to the conventional method of free skin grafting.